A Rational Policy Design or Contingent Historical Creation? Considering the Emergence of China's Distributed Solar Power Generation Regime. Issue 136 (4th July 2022) - Liu, Dawei
ABSTRACT: How did distributed solar power generation (DSPG) rise to prominence in China? Was there a causal link between China's industrial policies and its achievements in solar photovoltaic (PV)? Drawing on regime research, this article responds to such inquiries by delving deeply into the development course of this sector and thereby illuminating the role of policy 'niches'. Supplementing the dominant structural analyses that account for why industrial policies worked in China, insights generated from a regime analysis provide answers to the crucial question of how this specific industry came about and gained strength within China's governing system. It was found that as carriers of policy directives, demonstration projects functioned as niches and the pertinent fruits generated therein were converged into the constituent ingredients of the new DSPG regime. But, this process owes its success more to fortuity than rationality. A processual analysis focusing on niche and regime shaping sheds light on some latent and nebulous aspects of industrial management in China such as policy legacies, layering, patching, and contingency.